Unraveling the ‘female teacher effect’: The positioning and agency of female teachers in girls’ education reform - Morley, Alyssa (Education policy analysis archives, 2019)
Concerns about the academic performance of students from marginalized groups underscore calls for students to be taught by teachers of similar racial, ethnic, or gender identities (e.g., Miller, 2018). In sub-Saharan Africa, projects enlist women teachers as role models for girls in an effort to redress persistent gender disparities in education. However, in casting women teachers as inherent role models to girls, these projects run the risk of reinforcing long-standing portrayals of women in the Global South as a monolithic group with heightened responsibility for development (Chant, 2006; Mohanty, 1988). I identify one policy pilot in Malawi as a window for examining this phenomenon, and I pair discourse analysis and ethnographic analysis to investigate how women teachers are constructed in this policy and how these constructions unravel in practice. Drawing on anthropology of policy, I first trace how female teachers are created as particular types of “policy subjects” (Ball, Maguire, Braun, & Hoskins, 2011). Then, I examine how teachers at one school grapple with these narrowly constructed roles. This study’s findings caution against a disproportionate reliance on same-gender teachers for role-modelling, particularly when these teachers also belong to marginalized groups.